Compliance with remotely monitored physical therapy is higher in the older age group and for treatment of the upper extremity - Kanwar Parhar; Yousef Shishani; Abigail Berns; Reuben Gobezie; Patrick Denard (The Hive)
Background: Remotely monitored physical therapy (RMPT) has emerged as an efficacious and cost-effective alternative to in-office physical therapy. These platforms enable real-time progress tracking, adjustments to patient care plans, and provide feedback to motivate patients to improve their health status. However, little data is available with regards to compliance which may vary based on age given the technology required for use.